‘Just the Way it Was’- Perspectives on Sexual Harassment in Medical School and #MeToo of Women Graduating Prior to 1975 - Walling, Anne; Gillam, Morgan; Nilsen, Kari (Kansas Journal of Medicine, 2023)
Introduction.The purpose of this study was to assess gender-based mistreatment during medical education recalled by women who attended medical school between 1948 and 1975 and their perspectives on the #MeToo movement.Methods. Qualitative analysis of video-recorded structured interviews.Results.The 37 participants graduated in classes of 2-20% women. They described pervasive, multi-faceted gender-based mistreatment during training. Twenty (54%) disclosed personal experience of serious sexual mistreatment. Interviewees stressed that attitudes and behaviors toward women and trainees, now regarded as unacceptable, were previously widely accepted or tolerated. The majority (86%) expressed overall positive opinions of their training. Twenty-eight (76%) supported the #MeToo movement, four (11%) had negative opinions, and five (13.5%) were ambivalent or unwilling to comment. Seventeen (46%) were concerned that #MeToo damaged working relationships, twelve (32%) were concerned about overreach, and eight (22%) about false accusations.Conclusions.This group of older female physicians reported extensive experience of gender-based mistreatment and strong support of #MeToo. Nevertheless, about one quarter of the group did not support the #MeToo movement and even supporters expressed high rates of concern about the movement going too far, falsely accusing men of inappropriate behavior, and damaging working relationships. The interviewees did not want their medical training to be characterized as entirely negative, or to be portrayed as victims.